Morbid obesity increases death and dropout from the liver transplantation waiting list: A prospective cohort study. Issue 4 (26th April 2022) - Delacôte, Claire; Favre, Mathilde; El Amrani, Medhi; Ningarhari, Massih; Lemaitre, Elise; Ntandja‐Wandji, Line Carolle; Bauvin, Pierre; Boleslawski, Emmanuel; Millet, Guillaume; Truant, Stephanie; Mathurin, Philippe; Louvet, Alexandre; et al.
Abstract: Liver transplant (LT) candidates with a body mass index (BMI) over 40 kg/m 2 have lower access to a liver graft without clear explanation. Thus, we studied the impact of obesity on the waiting list (WL) and aimed to explore graft proposals and refusal. Method: Data between January 2007 and December 2017 were extracted from the French prospective national database: CRISTAL. Competing risk analyses were performed to evaluate predictors of receiving LT. Competitive events were (1) death/WL removal for disease aggravation or (2) improvement. The link between grade obesity, grafts propositions, and reason for refusal was studied. Results: 15, 184 patients were analysed: 10, 813 transplant, 2847 death/dropout for aggravation, 748 redirected for improvement, and 776 censored. Mortality/dropout were higher in BMI over 35 (18% vs. 14% 1 year after listing) than in other candidates. In multivariate analysis, BMI>35, age, hepatic encephalopathy, and ascites were independent predictors of death/dropout. Candidates with a BMI ≥ 35 kg/m 2 had reduced access to LT, without differences in graft proposals. However, grafts refusal was more frequent especially for 'morphological incompatibility' (14.9% vs. 12.7% p < 0.01). Conclusion: BMI over 35 kg/m 2 reduces access to LT with increased risk of dropout and mortality. Increased mortality and dropout could be due to a lower access to liver graft secondary to increased graft refusal for morphological incompatibility. Abstract :